Insane Therapy : Portrait of a Psychotherapy Cult. - Ayella, Marybeth (Temple University Press, 2010)
Sensational media coverage of groups like Heaven's Gate, the People's Temple, and Synanon is tinged with the suggestion that only crazy, lonely, or gullible people join cults. Cults attract people on the fringe of society, people already on the edge. Contrary to this public perception, Marybeth Ayella reveals how anyone seeking personal change in an intense community setting is susceptible to the lure of group influence. The book begins with the candid story of how one keen skeptic was recruited by Moonies in the 1970s--the author herself. Ayella's personal experience fueled her interest in.